Genetic diversity of octopus (Octopus cyanea) in the Northern Waters of Aceh - Ramadhaniaty Mutia; Damora Adrian; Moula Intania (BIO Web of Conferences)
The octopus exhibits highly developed defensive adaptations, including the ability to camouflage itself to deceive predators. It undergoes two larval stages, during which it experiences wide dispersal influenced by ocean currents and oceanographic characteristics. One region with complex current dynamics is the northern waters of Aceh, specifically around Pulau Aceh, which are influenced by the currents of the Indian Ocean and the Andaman Sea. The objective of this study is to assess the genetic diversity of Octopus cyanea by comparing the Aceh population with those from Sri Lanka and Japan, which are the closest geographically. The analysis was conducted using the COI gene with HCO and LCO primers. Results indicate that the Aceh population exhibits the highest genetic diversity, while the Sri Lanka population shows the lowest diversity. Populations with higher genetic diversity tend to have better survival prospects, suggesting that the Octopus cyanea population in Aceh is in a healthy condition. Furthermore, the study reveals that the Aceh population shares a close genetic relationship with the Japanese population, with a similarity value of 0.4. These two populations share haplotypes, indicating genetic connectivity. The mixing of haplotypes in the Japanese population is likely due to larval dispersal and varying current circulation, which influences species diversity.